2019
DOI: 10.3390/jfb10030039
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Recombinant Non-Hydroxylated Gelatin Mimetic in Pichia pastoris for Biomedical Applications

Abstract: Proteins derived from the natural extracellular matrix like collagen or gelatin are common in clinical research, where they are prized for their biocompatibility and bioactivity. Cells are able to adhere, grow and remodel scaffolds based on these materials. Usually, collagen and gelatin are sourced from animal material, risking pathogenic transmission and inconsistent batch-to-batch product quality. A recombinant production in yeast circumvents these disadvantages by ensuring production with a reproducible qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…3 a) below 200 nm (198 nm in this study) indicated that the RHLC had triple helical characteristics (Salvatore et al 2020 ). As the RHLC consisted of a triple-helix structure and did not have a terminal domain similar to extracted collagen, no significant peak appeared at 220 nm that displayed a beta-sheet (Gellermann et al 2019 ; Gibney et al 2021 ; Zhang et al 2019 ). The FTIR results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 a) below 200 nm (198 nm in this study) indicated that the RHLC had triple helical characteristics (Salvatore et al 2020 ). As the RHLC consisted of a triple-helix structure and did not have a terminal domain similar to extracted collagen, no significant peak appeared at 220 nm that displayed a beta-sheet (Gellermann et al 2019 ; Gibney et al 2021 ; Zhang et al 2019 ). The FTIR results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have tried to produce recombinant collagen molecules in different systems including bacteria, yeast and plant [25,[28][29][30][31]37,[43][44][45][46]. These recombinant proteins include full-length or fragments of collagen I, II, III and XXI at different hydroxylation levels (unhydroxylated or hydroxylated).…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, more and more effort has been put into recombinant collagen production as part of the rapid development of genetic engineering technology. Recombinant collagen molecules of different sizes have been expressed in all major expression platforms including mammalian cells, insect cells, yeast, bacteria and plant cells [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In general, high quality full-length collagen proteins have been produced in eukaryotic hosts but with very low productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers investigated plants, including tobacco, barley, and corn, as potential collagen-producing factories. Experiments with animals demonstrated the feasibility of producing collagens in the mammary glands of transgenic mice and eggs of transgenic chickens [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Recombinant Collagensmentioning
confidence: 99%